Presumption Of Innocence Towards Suspected Children Of Robbery - Zul Akli; Johari; Zainal Abidin; Sumiadi; Ummi Kalsum (International Journal of Law, Social Science, and Humanities, 2025)
This paper discusses the presumption of innocence principle, which in principle must be upheld in every legal case, especially where the alleged perpetrators are still children who are still in school, whose cases must receive special attention given that they are still developing and are easily influenced and prone to following others without clear reasons. The involvement of children in alleged robbery is a unique phenomenon in the Lhoseumawe area. The involvement of children in robbery cases is sometimes nothing more than a search for identity, as not all of them behave deviantly, but the effects of these actions have become a serious problem. In addition, they are not proven guilty when arrested and prosecuted, so they are returned to their parents. The education sector has its own rules for dealing with delinquent children, so sometimes the decisions made have an impact on the child's own education.